INVESTIGATION OF THE APOPTOSIS MECHANISM INDUCED BY TAXUS SUMATRANA EXTRACT LEAF IN CERVICAL CANCER CELLS - PUTRI, DESI EKA; ALMAHDY, ALMAHDY; PUTRA, YOZARWARDI USAMA; HAMIDI, DACHRIYANUS; WAHYUNI, FATMA SRI (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to investigate apoptosis pathways induced by T. sumatrana leaf extract, evaluate their impact on the modulation of p53 protein expression, and the regulation of Bax and Bcl-2 gene expression. Methods: The study included 3-5 experimental groups: untreated cells, T. sumatrana extract-treated cells (one or two concentrations), and paclitaxel-treated cells (one or two concentrations) as a positive control. The leaves were macerated in 70% ethanol to obtain the extract. Flow cytometry was employed to determine apoptosis rates and p53 protein expression. Real-time PCR was used to quantify the expression level of the Bax and Bcl-2 genes. ANOVA was utilized for statistical analysis to compare the mean differences among the groups. Results: Treatment with the T. sumatrana extract significantly increased the apoptosis rates in HELA cells (P<0.0001) and upregulated p53 protein expression compared to the untreated cells. The extract also increased Bax and decreased Bcl-2 expression, suggesting a shift towards a pro-apoptotic stage. The extract also increased Bax and decreased Bcl-2 expression, suggesting a shift towards a pro-apoptotic stage. The effects on apoptosis and p53 expression were comparable to paclitaxel at equivalent IC50 concentrations. Conclusion: The ethanol extract of T. sumatrana leaf promotes apoptosis in HELA cervical cancer cells by promoting p53 protein expression, increasing Bax, and decreasing Bcl-2 expression. These findings suggest its potential as an apoptosis-inducing agent, comparable to paclitaxel, and highlight its promise for further investigation in cervical cancer therapy.